Optical coherence tomography in differential diagnosis of optic neuropathy of various genesis - S.I. Zhukova; D.Yu. Samsonov; T.N. Yur’eva; T.V. Prozorova (РМЖ "Клиническая офтальмология")
S.I. Zhukova1, D.Yu. Samsonov1, T.N. Yurieva1–3, T.V. Prozorova1 1Irkutsk Branch of the S. Fyodorov Eye Microsurgery Federal State Institution, Irkutsk,   Russian Federation 2Irkutsk State Medical Academy of Professional Education — Branch of the Russian   Medical Academy of Continuous Professional Education, Irkutsk, Russian Federation 3Irkutsk State Medical University, Irkutsk, Russian Federation Background: although thinning of peripapillary retinal nerve fiber layer (RNFL) and macular ganglion cell complex (GCC) revealed by optical coherence tomography (OCT) are nonspecific data, they represent a key link in pathogenesis of optic neuropathy (ON) regardless of etiology. Aim: to identify differences between OCT patterns of RNFL and GCC damages associated with ON of different genesis. Patients and Methods: еxamination data of 58 patients with a suspected or preliminary diagnosed glaucoma who underwent an ophthalmic examination in a glaucoma department were retrospectively analyzed. According to the findings, 2 groups were formed. A Group 1 included 19 patients with an initial stage of primary open-angle glaucoma. 12 patients with altered RNFL and GCC, ineligible for glaucoma ON (GON), were enrolled in a non-glaucoma ON (non-GON) group. As a result of a detailed analysis of complaints, systemic and neurological status, chronic non-arteritic ischemic ON was diagnosed in 5 patients of the Group 2. In 7 patients, ON was associated with a history of optic neuritis with underlying multiple sclerosis (MS). Thus, we are faced with ONs associated with glaucoma, ischemia and MS. Considering a fundamentally different approach to treatment of these diseases and relevance of their differential diagnosis, a comparative analysis of ganglion cell axon topography was carried out in 3 groups in the light of the medical condition (1 — glaucoma-associated lesions, 2 — ischemia-associated lesions, 3 — MS-associated lesions). Results: the most pronounced RNFL alterations were observed in lower and temporal quadrants (GON patients); upper and nasal quadrants (ischemia patients); and in a temporal quadrant (MS patients). Retinal GCC lesions associated with GON and ischemia were asymmetric (superior defects in glaucoma patients vs. inferior defects in ischemia ones). MS-associated macular lesions were symmetrical and outstripped the RNFL alterations. Conclusion: different patterns of peripapillary RNFL and macular GCC damages are caused by pathogenesis of primary neuronal damage. These differences can be used as differential diagnostic criteria for GON and non-GON conditions in routine clinical practice. Keywords: optical coherence tomography, peripapillary retinal nerve fiber layer, macular ganglion cell complex, glaucoma ischemic optic neuropathy, non-arterial ischemic opticopathy, retrobulbar neuritis, multiple sclerosis. For citation: Zhukova S.I., Samsonov D.Yu., Yurieva T.N., Prozorova T.V. Optical coherence tomography in differential diagnosis of optic neuropathy of various genesis. Russian Journal of Clinical Ophthalmology. 2024;24(4):170–176 (in Russ.). DOI: 10.32364/2311-7729-2024-24-4-2